Cash Waqf and Crowdfunding: A Study of Online-Based Cash Waqf in The Passive Charity of The Indonesian Waqf Education Foundation - Fahmi, Mochammad Dzul; Abdul Majid, Muhammad; Qaseem, Fazlullah Ihza (Muslim Business and Economics Review, 2025)
This research examines the effectiveness of crowdfunding for online-based cash waqf by analysing the cash waqf turnover practice of the Indonesian Waqf Education Foundation's Pasif Amal (Passive Charity) website. Two topics are explored in this research. First, how the Indonesian Waqf Education Fund practices cash waqf crowdfunding strategies for passive charity. Second, the effectiveness of the cash waqf crowdfunding strategy and the implications for the legalization of cash waqf. This research uses a qualitative method with the approach of Soerjono Soekanto's legal effectiveness. This research concludes through its passive crowdfunding strategy, the Indonesian Waqf Education Foundation has changed the previously-dominant view that waqf is limited to land; instead, the Foundation’s experience illustrates that waqf can also represent goods in the form of money. The findings confirm that passive charitable institutions are effective and can even become a new approach in the world of waqf, especially in countries where cash waqf is already a legal practice.